Pregnancy outcomes in patients with systemic lupus erythematosus hospitalized in Imam Reza teaching hospital (Kermanshah, Iran) - Anisodowleh Nankali; Maryam Hemati; Hamidreza Safari; Fariba Najafi (Mashhad University of Medical Sciences, 2019)
Introduction: Systemic lupus erythematosus (SLE) is a common autoimmune disease and predominantly affects fertile women. This disease is associated with multisystem involvement and has high risk for both the mother and the fetus. One of the major risks for SLE mothers is the occurrence of disease flare during pregnancy. Some studies have shown that SLE flares more during pregnancy, but the conclusion of others is quite the opposite. Therefore, this study was performed with aim to determine the feto-maternal outcome in pregnant women with SLE. Methods: This retrospective study was performed on 38 pregnant women with lupus who were hospitalized in Obstetrics and Gynecology ward of Kermanshah Imam Reza hospital in 2008-2012. The renal parameters including creatinine and urinary protein excretion, hemoglobin and platelet levels, and also pregnancy outcomes- preeclampsia, eclampsia, abortion, preterm delivery, mode of delivery, infant's weight and stillbirth were recorded. Data collection tool was a questionnaire which was designed based on the main goals of the study. Data were analyzed by SPSS software (version 16) and descriptive statistics index. P<0.05 was considered significant. Results: In this study, there was cesarean section in 27 patients (73.68%), abortion in 8 (21.05%), intrauterine deaths in 2 (2.64%), hypertension in 9 (23.68%) and eclampsia in 1 (2.63%). Preterm delivery occurred in 22 patients (57.89%). Mean 24-hour urine protein was 185.321 mg and mean of birth weight was 2248.57 gr. Conclusion: Lupus and pregnancy are associated with pregnancy unfavorable outcomes including preeclampsia, preterm delivery, high occurrence of cesarean section and abortion.